1998
DOI: 10.1088/0022-3727/31/12/014
|View full text |Cite
|
Sign up to set email alerts
|

A solid-state photovoltaic cell sensitized with a ruthenium bipyridyl complex

Abstract: Ruthenium bipyridyl complexes have been used as efficient sensitizers for photoelectrochemical cells based on nano-porous films of . It is found that cis-dithiocyanate-bis(2,2-bipyridyl-4,4-dicarboxylate) ruthenium (II) can be used as the sensitizer in a solid-state photovoltaic cell in which a monolayer of the sensitizer is sandwiched between nano-porous n- and p-CuI. The data on performance of the cell and the problems encountered in construction of dye-sensitized solid-state photovoltaic cells are describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
135
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(139 citation statements)
references
References 14 publications
(21 reference statements)
3
135
0
1
Order By: Relevance
“…In 1995, Tennakone et al first demonstrated an SSDSC based on CuI HTM in conjunction with cyanidin dye [54], which was later improved by replacement with a Ru-bipyridyl complex dye, showing a PCE of 4.5% [55]. There have been several strategies for photovoltaic performance enhancement.…”
Section: Cuimentioning
confidence: 99%
“…In 1995, Tennakone et al first demonstrated an SSDSC based on CuI HTM in conjunction with cyanidin dye [54], which was later improved by replacement with a Ru-bipyridyl complex dye, showing a PCE of 4.5% [55]. There have been several strategies for photovoltaic performance enhancement.…”
Section: Cuimentioning
confidence: 99%
“…The short-circuit current density reached about 1.5-2.0 mAcm -2 in sunlight (about 800 Wm -2 ), however, they found that the polarization arising from mobile Cu + ions tends to decrease the open-circuit voltage of the cell. By replacing cyanidin with a Ru-bipyridyl complex dye, they (Tennakone et al, 1998) then fabricated a solid-state DSC with the structure of TiO 2 /Ru(II)(dcbpy) 2 (SCN) 2 /CuI in 1998. The efficiency and the stability of the solid-state DSC was less than those of the typical DSCs.…”
Section: P-type Semiconductor Nanoparticles As Solid-state Electrolytesmentioning
confidence: 99%
“…Nanocrystalline TiO 2 films were formed by the hydrolysis of titanium isopropoxide according to the literature [20,23]. Thus, 0.5 mL of titanium isopropoxide (Aldrich, 99 %) was slowly added with vigorous stirring to a mixture of 2.5 mL of glacial acetic acid (Sigma Aldrich), 7.5 mL of isopropanol (Sigma Aldrich) and 2.5 mL of deionized water under argon atmosphere.…”
Section: Device Preparation and Characterizationsmentioning
confidence: 99%